2019
DOI: 10.33607/bjshs.v2i113.787
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Health Literacy, Physical Activity, Motivation and Barriers of People Aged 30–50 Years

Abstract: Background. An international study of health literacy among European citizens has shown that 47% of Europeans lack health literacy (Sørensen et al., 2015). Participation in physical activity is associated with health literacy. According to Matsushita, Harada, and Arao (2018), people with a lack of health literacy are less engaged in physical activity.The aim of this study was to evaluate health literacy, physical activity, motivation of people aged 30 to 50 years and barriers to be physically active, so that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…It revealed that limited health literacy was associated with poor health status, having more than one long-term illness and the higher use of health care services involving six or more consultations with doctors in the last 12 months [4]. Other studies, in which national versions of the HL questionnaire developed within the HLS-EU project were used, confirmed that low HL may be associated with people's poor self-assessment of health status [12,20], the prevalence of long-term illnesses [12], the higher utilisation of health care resources [14,21], and a lower level of physical activity [22][23][24].Although the scope of information which arises from the HLS-EU-Q47 is extensive, it appears that the size of the tool may result in reduced compliance of respondents, especially if the questionnaire is used as a part of a survey which is also focused on other issues. Therefore, a shortened but also validated, the 16-item version has been used in many surveys (HLS-EU-Q16) [5,12,[25][26][27][28][29].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…It revealed that limited health literacy was associated with poor health status, having more than one long-term illness and the higher use of health care services involving six or more consultations with doctors in the last 12 months [4]. Other studies, in which national versions of the HL questionnaire developed within the HLS-EU project were used, confirmed that low HL may be associated with people's poor self-assessment of health status [12,20], the prevalence of long-term illnesses [12], the higher utilisation of health care resources [14,21], and a lower level of physical activity [22][23][24].Although the scope of information which arises from the HLS-EU-Q47 is extensive, it appears that the size of the tool may result in reduced compliance of respondents, especially if the questionnaire is used as a part of a survey which is also focused on other issues. Therefore, a shortened but also validated, the 16-item version has been used in many surveys (HLS-EU-Q16) [5,12,[25][26][27][28][29].…”
mentioning
confidence: 94%
“…It revealed that limited health literacy was associated with poor health status, having more than one long-term illness and the higher use of health care services involving six or more consultations with doctors in the last 12 months [4]. Other studies, in which national versions of the HL questionnaire developed within the HLS-EU project were used, confirmed that low HL may be associated with people's poor self-assessment of health status [12,20], the prevalence of long-term illnesses [12], the higher utilisation of health care resources [14,21], and a lower level of physical activity [22][23][24].…”
mentioning
confidence: 94%
“…Similarly, physical literacy can be described as a disposition to take advantage of embodied human capacity in which the individual has the motivation, confidence, physical competence, knowledge, and understanding to value and take responsibility for maintaining meaningful physical activity throughout life [ 93 ]. It has been shown that active people have a higher health literacy than inactive people [ 94 ]. In addition to providing monitoring of activities to increase physical activity, a comprehensive approach could also focus on health and physical literacy.…”
Section: Limits Of Activity Tracker In Clinical Practicesmentioning
confidence: 99%
“…People are discouraged from exercising on a regular basis due to a variety of personal and environmental variables. According to research people that have less desire to engage in physical activity (Valatkaitytė and Česnaitienė, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Motivation is the most important component affecting selfdetermination and encouraging physical activity. Motivation is defined by psychologists as a need or desire that energizes and leads action toward a goal (Valatkaitytė and Česnaitienė, 2019).…”
Section: Introductionmentioning
confidence: 99%